2016
DOI: 10.1111/bjh.14424
|View full text |Cite
|
Sign up to set email alerts
|

The severity of anaemia depletes cerebrovascular dilatory reserve in children with sickle cell disease: a quantitative magnetic resonance imaging study

Abstract: Overt ischaemic stroke is one of the most devastating complications in children with sickle cell disease (SCD). The compensatory response to anaemia in SCD includes an increase in cerebral blood flow (CBF) by accessing cerebrovascular dilatory reserve. Exhaustion of dilatory reserve secondary to anaemic stress may lead to cerebral ischaemia. The purpose of this study was to investigate CBF and cerebrovascular reactivity (CVR) using magnetic resonance imaging (MRI) in children with SCD and to correlate these wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
67
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 33 publications
7
67
0
1
Order By: Relevance
“…A significant relationship was also found between skew and kurtosis mean diffusivity histogram measures and CVR in healthy controls. This research group has previously shown that CVR was significantly reduced in children with SCD and that lower CVR in this population is associated with lower hematocrit levels and region‐specific cortical thinning (Kim et al , ; Kosinski et al , ). Taken together, these findings suggest that reduced CVR is associated with changes in white matter seen in children with SCD and that the beneficial effects of hydroxycarbamide on anaemia may contribute to improvements in CVR and white matter microstructural integrity.…”
mentioning
confidence: 95%
“…A significant relationship was also found between skew and kurtosis mean diffusivity histogram measures and CVR in healthy controls. This research group has previously shown that CVR was significantly reduced in children with SCD and that lower CVR in this population is associated with lower hematocrit levels and region‐specific cortical thinning (Kim et al , ; Kosinski et al , ). Taken together, these findings suggest that reduced CVR is associated with changes in white matter seen in children with SCD and that the beneficial effects of hydroxycarbamide on anaemia may contribute to improvements in CVR and white matter microstructural integrity.…”
mentioning
confidence: 95%
“…The STOP (Stroke Prevention Trial in Sickle Cell Anaemia) clinical trial of transfusion in SCD demonstrated the association between increased CBF velocities as detected by Transcranial Doppler scan (TCD) and stroke risk (Adams et al, 1998). Kosinski et al (2016) provide evidence that cerebrovascular reactivity (CVR) is related to the severity of anaemia in SCD. Children without stroke were randomly assigned to treatment with blood transfusion or no (standard) treatment.…”
mentioning
confidence: 99%
“…But these two risk factors do not correlate directly with the 'occlusive vascular' and the 'haemodynamic ischaemic' models of stroke discussed above. The children included in the study reported by Kosinski et al (2016) did not have steno-occlusive disease (although disease of the neck vessels may not have been completely excluded) but presumably, the exhausted cerebrovascular reserve in vessels distal to areas of stenosis only further heightens stroke risk in affected children. Children with TCD velocities >170 cm/s had a stroke risk of 7% over 36 months and children with TCD velocities >200 cm/s had a stroke risk of 40% over 36 months.…”
mentioning
confidence: 99%
See 2 more Smart Citations